The impact of providing fruits and vegetables to socially disadvantaged men. Issue 4 (4th July 2019) - Depa, Julia; Wolf, Amelie; Rössler, Valeska; Weiffenbach, Jana; Hilzendegen, Carolin; Stroebele-Benschop, Nanette
ABSTRACT: Worldwide, food banks offer foods for free (e.g. USA) or at nominal costs (e.g. Germany), to people in need, but nothing is known about their impact on fruit and vegetable (FV) intake. Study aims were to examine whether (1) German male food bank users have a higher FV intake (variety and amount) compared to non-food bank users and whether (2) providing fresh FV for free, which participants personally selected, can increase FV intake among men in dependence of their food bank use. For the first question, a cross-sectional design and for the second, a longitudinal design (randomized intervention study) were chosen. Sociodemographic variables and dietary patterns (Food Frequency questionnaire and FV variety questionnaire) were assessed at baseline and dietary patterns were evaluated again after the intervention. The intervention consisted of providing two daily portions of fresh FV each week for 4 weeks. In total, 52 men participated. Men using a food bank regularly consumed a significantly larger FV variety than non-food bank or infrequent food bank users. The provision of free FV improved intake among social disadvantaged men, whereby particularly non-food bank users benefited from the intervention. Using a food bank that offers fresh produce might be a promising public health approach.